OPTIMALISASI PENENTUAN BIAYA MINIMUM PADA PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN MENGGUNAKAN METODE DYNAMIC PROGRAMMING (STUDI KASUS DI PT. XYZ) - Vivin Nur Oktavianty; Tedjo Sukmono (Spektrum Industri, 2020)
PT. XYZ is a manufacturing company that produces semi-finished goods, that isÂ imitation leather (PVC). This company has inventory problem in their production process, that is raw material shortages. Â The purpose of this study was to determine the amount of calcium carbonate raw materials purchased by PT. XYZ with optimal costs. Before using this Dynamic Programming, the cost of buying raw materials is Rp. 7,345,000,000. From the results of planning the purchase of raw materials for the next 12 periods (January-December 2018) are 1184, 1185.5, 1187.1, 1188.6, 1190.1, 1191.6, 1193.2, 1194.7, 1196.2, 1197.7, 1199.3 and 1200.8 Tons. To compile a production plan by minimizing total production costs, the dynamic programming method is used with the objective function Min Fn(In) = . As a result, the total purchase cost of calcium carbonate raw material is a minimum of Rp. 7,154,355,000. After calculating the cost, it can be seen that after using the dynamic programming method the profits obtained by the company Rp. 114,472,000 compared to before using the dynamic programming method Rp. 111,040,000.